A Moderation Model of Family Environment in the Relationship Between Financial Literacy and Risk Perception on Stock Investment Decisions for Young Couples in Denpasar City - WULANDARI, I Gusti Ayu Athina; PUTRA, I Komang; PRAMARTHA, I Made Aditya (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to determine the moderating effect of family environment on the relationship between financial literacy and risk perception on stock investment decisions for young couples in Denpasar City. The population in this study were all young married couples in Denpasar City. The technique used in selecting samples for this study was a nonprobability sampling method with a purposive sampling technique. The criteria included in the sample category are young people who are married and married, which obtained a sample of 168 people. The data analysis technique used in this study is Moderated Regression Analysis (MRA) using the SPSS (Statistical Product and Service Solution) program. The results showed that financial literation and risk perception positively affect the stock investment decisions of young couples in Denpasar City. It means that the higher the level of understanding of financial literacy and understanding of risk perception owned by young couples in Denpasar City, the stronger the decision to invest in stocks. In addition, it is known that the family environment cannot moderate the financial literation factor. However, the family environment can moderate the risk perception variable, weakening the understanding of risk perception on the stock investment decisions of young couples in Denpasar City.